Perspektif Mahasiswa PBSI FKIP UNRI Terhadap Kecerdasan Buatan (AI) Dalam Pembelajaran Sastra Sebagai Ancaman dan Kolaborasi Kreatif - Laia, Jarianis; Mardhotillah, Elsa; Yurike, Mudia; Arrahmi, Nayla (Innovative: Journal Of Social Science Research, 2025)
The emergence of artificial intelligence (AI) in the field of literature has sparked discussions regarding its role and influence on human mahaiscreativity, especially among students. Indonesian Language and Literature Education Study Program (PBSI) FKIP Riau University. This research aims to explore the views of PBSI students regarding AI's ability to create literary works and its impact on originality and creativity. Through a survey involving 100 respondents, this research found that the majority of students think that AI cannot completely replace humans in the literary creation process, because true literary works require deep emotional understanding and cultural context. However, students also see AI as a tool that has the potential to increase creativity and collaboration in writing. These findings suggest that AI is not a threat to human literary creation, but rather an opportunity to expand the boundaries of creativity. Thus, this article provides important insights into how PBSI students can utilize AI wisely in their creative processes, as well as the implications for literary education in the digital era.